Przesłanki rozwiązania parlamentu w praktyce ustrojowej V Republiki Francuskiej - Jakubiak, Łukasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The paper discusses the grounds required for the dissolution of the parliament in the political practice of the French Fifth Republic. The Constitution of October 4, 1958 adopted a model of strengthened political power of the head of state, granting them instruments of executive influence on the functioning of other state organs. Paragraph 12 of the Constitution gives the President practically unlimited power to dissolve the National Assembly – the lower chamber of French parliament. The conditions for applying this paragraph are not stipulated in the legal regulations. It is not necessary for the President to respond to a motion of another body, or even to obtain a countersignature. These constitutional factors have led to various political practices. The author of the paper puts forward the thesis that giving freedom to the head of state as regards the application of paragraph 12 on the one hand provides the necessary foundations to exercise a power model with a considerable degree of decisiveness, but on the other may lead to a situation where the dissolution of the National Assembly no longer has a power function in its conventional sense, but serves the purpose of providing the head of state with an instrument for considerably strengthening his own political position. Since the present Constitution of the Fifth Republic has been in force, the National Assembly has been dissolved five times. The author identifies three basic grounds for applying paragraph 12: to defuse a political or social conflict (1962 and 1968), to restore a politically homogenous executive power (1981 and 1988), and to maintain a given political configuration (1997). Since the 1980s the dissolution of parliament has become a tool for the president to avoid cohabitation and, by this token, to provide a political system where the role of the leader of the executive is in the hands of the head of state. On account of the defeat of the formation supporting the president in 1997 this strategy failed to produce the expected outcome. The dissolution of the National Assembly has not taken place since. In 2000, the length of the mandate of the head of state was shortened to five years, which makes it more likely for parliamentary elections to occur directly after presidential elections. This may for a long time to come eliminate the main grounds for the dissolution of the lower chamber, which in the 1980s and 1990s stemmed from the desire to ensure a political system favorable for the head of state. This reason alone may mean that the significance of paragraph 12 in the political practice of the Fifth Republic will continue to be limited.
Grounds for the dissolution of parliament in the French Fifth Republic’s political practice
Keywords: Francja; V Republika; rozwiązanie parlamentu; Zgromadzenie Narodowe; arbitraż; prezydent Republiki